Occurrence of Ectoparasite on Small Mammals between Disturbed and Undisturbed Area of Peat Swamp Forest in Ayer Hitam Utara Reserve Forest - Kong, Khei Khiong; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2025)
The Ayer Hitam Utara Forest Reserve (AHUFR) is situated in Peninsular Malaysia's Muar district in Johor (1° 52' North, 103° 11' East) and this region, which spans around 3,797 hectares (ha), is recognised as the largest and last peat swamp forest. This study aimed to identify the various species of small mammals and ectoparasites and evaluate ectoparasites prevalence on ectoparasites between disturbed and undisturbed areas of AHUFR for a total of 12 sampling days. Sampling involved 24 cage traps and four mist nets across two sampling sites in each disturbed and undisturbed areas. Four species were recorded: Tupaia glis (Common Treeshrew), Leopoldamys sabanus (Long-tailed Giant Rat), Maxomys rajah (Rajah Spiny Rat), and Rhinolophus trifoliatus (Trefoil Horseshoe Bat). Total of seven different species of ectoparasites were sampled which are Haemaphysalis concinna, Amblyomma sp., Haemaphysalis sp., Laelaps nutalli, Ixodes granulatus, Ixodes sp., and unknown species. While undisturbed area has higher individual number of ectoparasites (59) while only 2 species, disturbed area has higher species number (7) with 21 total individuals. The disturbed area exhibited a higher Shannon-Weiner index and evenness and a T-test indicated no statistically significant difference between the areas. The findings can provide baseline data for future research and conservation efforts.